Pengaruh Kemampuan Kerja, Komitmen Organisasi Dan Disiplin Kerja Terhadap Produktivitas Kerja Pegawai Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Bima - Wardah, Sri; Rahmatiah, Rahmatiah; Badar, Muh. (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of communication and workload on employee work effectiveness at the Department of Population and Civil Registration of Bima Regency. The research is motivated by the low level of work effectiveness, indicated by insufficient interaction among employees and the unbalanced distribution of workload. The study applies a quantitative approach with an associative method. The population consists of all 69 employees of the Department of Population and Civil Registration of Bima Regency, and the entire population was taken as the sample using a saturated sampling technique. Data were collected through a closed-ended questionnaire with a Likert scale and analyzed using multiple linear regression with the assistance of SPSS. The results show that communication has a positive and significant effect on work effectiveness, while workload has no significant effect when tested partially. However, simultaneously, communication and workload significantly influence employee work effectiveness. The coefficient of determination (R²) of 32.3% indicates that communication and workload contribute to work effectiveness, while the remaining 67.7% is influenced by other factors not examined in this study. This study concludes that improving employee work effectiveness can be achieved through more intensive communication among employees, such as regular meetings and team coordination, as well as a more proportional distribution of workload.